SISTEM PENGATURAN DISSOLVE OKSIGEN MENGGUNAKAN AERATOR PADA IKAN KOI DENGAN METODE FUZZY - Faisal Maulana Ibrahim; n/a Rahmadwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Aerator is a machine that produces air bubbles that functions to move water in the pond so that the water is rich in dissolved oxygen which is needed by all freshwater fish. The working principle of this tool is to make the surface of the water as much as possible in contact with the air. The goal is that the oxygen content in the water is sufficient and gases and impurities that usually cause rot can be expelled from the water. These air bubbles are very important for fish because these bubbles act as oxygen for fish. This oxygen level is commonly called DO (dissolved oxygen). Many ornamental fish entrepreneurs, especially koi, underestimate the level of dissolved oxygen in water (the use of aerators) both in terms of power consumption, which is not regulated or does not provide a tool in the form of an aerator. For this reason, this research makes aerator speed settings according to the needs of the fish and also saves costs because it does not have to be turned on every time.Keywords: Aerator, koi fish farming, DO, dissolved oxygen in water